Karnaval Sunatan Massal di Sooko Mojokerto: Ritual, Solidaritas, dan Transformasi Sosial Keagamaan - Amanda Bunga Diana Putri Fauziyah; Agus Machfud Fauzi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2025)
Mass circumcision in Sooko, Mojokerto, East Java, is no longer limited to the fulfillment of religious obligations, but has evolved into a lively village carnival. This study examines how the transitional rites that were originally private were reconfigured into public celebrations and how these changes reflect the shifting relationship between religion, culture, and the life of rural communities in Java. The research uses a qualitative-interpretive design with an ethnographic case study. Data were collected through participatory observation, semi-structured interviews with religious leaders, committees, village officials, circumcision participants, and parents, tracing of documents and photo archives, and digital ethnography of residents' social media content. The analysis uses an interactive model through data condensation, presentation, and verification, with credibility strengthened through triangulation, member checking, and audit trails. The results of the study show four main findings: first, carnival reproduces the three phases of the rite of transition through separation, liminality, and reintegration, with the procession extending the liminal phase as well as transforming the experience of pain into a collective honor; second, preparation of cross-neighborhood harmony to strengthen social capital through reciprocity and community networks; third, religious authority is negotiated through the boundary between festivity and piety; and fourth, mediatization expands the reach of tradition while presenting cost, noise, and spectacle pressures. The research resulted in a Before–After transformation model based on a multi-level framework that connects the dynamics of individuals, communities, and public-digital spaces.